Nekatere značilnosti lokalne klime v Zagorski dolini - Vrtačnik Garbas, Katja (Geografski vestnik, 2004)
The main factor of the local climate in the Zagorje valley is the relief which via different altitudes, exposition and inclination has an impact on temperatures, precipitations, insolation and windiness. Besides, it represents the basis for development of a temperature inversion and radiation fog connected with it. As a consequence, the minimum temperatures in the thermal zone, which starts approximately at the altitude of 400-500 m, are higher than at the bottom of the valley. This fact together with the exposition and the altitude influences on the phenophases of plants, snow cover retention, duration of insolation, agriculture, settlement and eventually also on air pollution which was in the nearby past one of the most urgent problems in the Zagorje valley.
Keywords: klimatogeografija; microclimate; mikroklima; relief; topography; temperatura; temperaturni obrat; Zasavje; Central Sava Valley; Sava Hills; Posavsko hribovje